2020
DOI: 10.1186/s12943-020-01208-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circSHKBP1 promotes gastric cancer progression via regulating the miR-582-3p/HUR/VEGF axis and suppressing HSP90 degradation

Abstract: Background: Circular RNAs (circRNAs) play important regulatory roles in the development of various cancers. However, biological functions and the underlying molecular mechanism of circRNAs in gastric cancer (GC) remain obscure. Methods: Differentially expressed circRNAs were identified by RNA sequencing. The biological functions of circSHKBP1 in GC were investigated by a series of in vitro and in vivo experiments. The expression of circSHKBP1 was evaluated using quantitative real-time PCR and RNA in situ hybri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
249
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 287 publications
(256 citation statements)
references
References 33 publications
6
249
0
1
Order By: Relevance
“…Prognostic biomarkers refer to biomarkers related to prognosis of cancer patients, and they can be gene expression (mRNA), protein content or small molecular metabolites [ 28 ]. As prognostic markers can be independent to determine the prognosis of patients and assist the diagnosis and treatment of cancer in clinical practice, searching for prognostic markers related to cancer prognosis has become a hot research topic [ 29 – 31 ]. Many experiments have been conducted to screen and explore prognostic markers of GC, among which the most famous one is PD-L1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic biomarkers refer to biomarkers related to prognosis of cancer patients, and they can be gene expression (mRNA), protein content or small molecular metabolites [ 28 ]. As prognostic markers can be independent to determine the prognosis of patients and assist the diagnosis and treatment of cancer in clinical practice, searching for prognostic markers related to cancer prognosis has become a hot research topic [ 29 – 31 ]. Many experiments have been conducted to screen and explore prognostic markers of GC, among which the most famous one is PD-L1 gene.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that circRNAs are a large class of widespread and diverse endogenous RNAs in animals that play critical roles in many physiological and pathological processes, including fat (Jiang et al, 2020), muscle (Zhang P. et al, 2019), and cancer (Xie et al, 2020) development. For example, Jiang et al (2020) characterized the expression profile of circRNA in fat tissue during developmental stages of the calf and adult cow and demonstrated that the circFUT10 regulates adipocyte cell proliferation and differentiation by sponging the miRNA let-7c (Jiang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It promotes GC tumorigenesis by regulating the miR-140-3p/YY1 signaling axis (Zhang L. et al, 2020). CircSHKBP1 was overexpressed in tumors and serum exosomes of GC patients, and it correlated with advanced pathological staging and poor OS (Xie M. et al, 2020). CircSHKBP1 promotes GC progression by sponging miR-582-3p to increase HuR levels and promoting VEGF stability, and also by binding HSP90 to prevent its interaction with STUB1 (Xie M. et al, 2020).…”
Section: Gastric Cancer (Gc)mentioning
confidence: 99%